Perancangan E-Learning Menggunakan Framework Codeigniter di SMAN 1 Candung - Amini, Lisa; Zakir, Supratman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is based on the need for online learning media (E-learning) at SMAN 1 Candung,where teachers have not used online learning media to assist teachers in delivering material tostudents if teachers cannot attend the lesson. The limited time learning in class also makes thematerial delivered is also limited.‎ The research method used is the Research and Development(R&D) method, which is a research method to produce a product, the R&D model used is the 4Dversion, namely, define, design, develop, and deploy, with the system development model using the Develop Life Cycle System. (SDLC) by applying the Waterfall model which consists of Communication, Planning, Modeling, Construction and Deployment.‎ Research Based on theresearch conducted, the researcher succeeded in making e-learning products at SMAN 1 Candung.The results of the validity test conducted by computer experts on this product are very valid with a value of 0.91. The results of the